ETIKA BISNIS MENURUT AL-GHAZALI: TELAAH KITAB IHYA’ ’ ULUM AL-DIN - Sopingi, Imam (Fakultas Ekonomi, UIN Maliki Malang, 2014)
This article study the business ethics according of al-Ghazali which can be found among its bookihya’ ’ulum al-din, according for him is not properly by merchant only focussed its view to just world, byforgetting eternity. If that happened that way, hence its age will without effect. On the contrary for sensiblesuggested to look after the himself by taking care of its capital. And capital of human being in this life isreligion and business of exist in its. Al-Ghazali divide the business ethics become seven, that is; straighteningintention in have business, intention to do the fardu kifayah, besides paying attention to world market alsopay attention to the eternity market, when transacting in Market always remember the Allah, do not tooambition in have business, avoiding and leaving business which syubhat of and surely illicit, and ever take acare the evaluation in have business to don’t harm others. While valuable transaction of kindliness, al-Ghazalidivide the ethics become six, that is; practicing on to the manner born, do not complicate if transacting atpauper, doing a kindness moment bill for the debt, doing a kindness moment pay for the debt, cancelingtransaction of seller moment get the loss, giving payment diffuseness for clan faqir and impecunious